Flexible conductive water-based adhesive and its use

CN117747823BActive Publication Date: 2026-11-03EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311601106.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-11-03
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

现有电极粘结剂在电池循环过程中无法有效适应机械应力,导致电极粉碎和容量损失,同时导电性差限制了快速充放电能力,且机械共混导电粘结剂存在分散不均问题。

Method used

A flexible conductive aqueous binder with a core-shell structure was prepared by emulsion polymerization and electrostatic doping. The core is a flexible copolymer and the shell is a conductive polymer. By forming a uniform conductive network, the toughness and conductivity of the electrode are improved.

Benefits of technology

It achieves a combination of high conductivity and high toughness, adapts to the volume deformation of the electrode during charging and discharging, improves the cycle stability and rate performance of the battery, suppresses the shuttle effect, and improves the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a flexible conductive water-based binder and application thereof, and the flexible conductive water-based binder is prepared into a water emulsion with a core-shell structure by adopting emulsion polymerization and an electrostatic doping method. The core is a flexible copolymer, and the shell is a conductive polymer, so that the conductivity and high toughness of the binder can be realized simultaneously. The high toughness gives the binder the ability to adapt to the volume deformation in the charging and discharging process of a sulfur positive electrode, and the conductivity reduces the internal resistance of the electrode, and both are beneficial to improving the electrochemical stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy materials technology, and more specifically, to a flexible conductive water-based binder and its application. Background Technology

[0002] With the increasing demand for high-performance batteries in portable electronic devices and electric vehicles, the pursuit of electrodes with high energy density and long cycle life is receiving increasing attention. However, electrodes are sensitive to the mechanical stress generated during cycling, especially those based on conversion and alloying reactions. Once the bonding strength cannot accommodate volume expansion, pulverization occurs, leading to a sharp loss of capacity. Considering this, polymer binder materials, acting as a bridge between electrode particles and current collectors, are crucial.

[0003] Currently, widely reported electrode binders are mainly linear polymers. However, due to the easy swelling and dissolution of organic electrolytes and the weak inter-chain interactions, ordinary linear polymer binders cannot provide significant mechanical properties to adapt to the stress / strain during repeated discharge / charge processes. Therefore, in recent years, polymer binders with 3D network structures have been considered one of the preferred binders for stabilizing and maintaining the overall electrode structure due to their strong inter-chain interactions. Patent CN111092226 A discloses a method of mixing polyacrylic acid with ethanolamine or triethanolamine, which deprotonates the polyacrylic acid, disrupting the strong hydrogen bonds within the polyacrylic acid molecule. After the polymer chains extend, they interweave to form a three-dimensional network. At the same time, due to the hydrogen bonding between the amine cations, the three-dimensional network structure is strengthened, which can effectively maintain the stability of the electrode structure during cycling, buffer volume changes, and prevent the active material from falling off the current collector.

[0004] Furthermore, while addressing the electrode expansion issue is crucial, we must also consider the inherently poor conductivity of sulfur cathodes, which inhibits their rapid charge-discharge capability, especially at high mass loadings. Patent CN 115995557 A discloses the preparation of conductive binders by mechanically mixing modified carbon nanotube aqueous dispersions with acrylic multi-component copolymers. Although the conductive binders prepared above possess a certain degree of conductivity, mechanically blended conductive binders suffer from uneven dispersion and sedimentation issues in practical applications, which severely impact electrode performance.

[0005] Therefore, flexible aqueous binders that achieve uniform conductive networks are one of the most effective strategies for constructing electrodes with high energy density and long cycle life. Summary of the Invention

[0006] To address the issues of volume expansion, release of byproducts, and insulation properties of active materials, this application provides a flexible conductive aqueous adhesive. The adhesive film exhibits an elongation at break exceeding 80% and an electronic conductivity exceeding 0.8 S / cm. -1 This binder is a water emulsion with a core-shell structure, prepared by emulsion polymerization and electrostatic doping. The core is a flexible copolymer, and the shell is a conductive polymer, achieving both high conductivity and high toughness. High toughness enables it to adapt to volume deformation during charging and discharging of sulfur cathodes and silicon anodes, while high conductivity reduces electrode internal resistance. Both of these properties contribute to improving the battery's cycle stability, rate performance, and other electrochemical performance.

[0007] Furthermore, the flexible conductive water-based adhesive is prepared by the following method, including the following steps: (1) Under an inert atmosphere, 0.1-0.3 parts by mass of emulsifier, 0.1-0.2 parts by mass of reducing component of redox initiator, 0.1-0.5 parts by mass of crosslinking agent, 15-30 parts by mass of unsaturated sulfonate monomer, 30-60 parts by mass of acrylate monomer, 25-40 parts by mass of unsaturated monomer with excellent resistance to organic electrolyte and deionized water are uniformly mixed and emulsified. After heating to 30-70°C, 0.2-0.4 parts by mass of oxidizing component of redox initiator is added. After reacting for 4-8 hours, 0.2-0.4 parts by mass of oxidizing component of redox initiator and 0.1-0.2 parts by mass of reducing component of redox initiator are added. The reaction is continued for 6-12 hours to obtain a macromolecular doped emulsion with a solid content of 25 wt%-40 wt%. (2) Under an inert atmosphere, 2-6 parts of thiophene monomer are doped into 94-98 parts of macromolecular doped emulsion, and 2-5 parts of oxidant are added. The mixture is stirred and reacted at 0-20°C for 24-72 hours to obtain a conductive polymer emulsion with a solid content of 15 wt%-30 wt%. The emulsion is then purified by adsorption with chelating resin and dialysis. The conductive polymer emulsion is then subjected to secondary doping with 5% dimethyl sulfoxide and mixed with deionized water at room temperature to prepare a 5 wt% flexible conductive waterborne binder.

[0008] A second aspect of the present invention provides the application of a flexible conductive aqueous binder, namely an electrode sheet, comprising a current collector and a slurry, wherein the slurry comprises an active material, a binder, a dispersant and a conductive agent, and the binder is the binder described in the first aspect above.

[0009] Furthermore, the application of the flexible conductive water-based binder allows for the preparation of electrode sheets via the following method, including the following steps: Active material, conductive agent, and flexible conductive water-based binder are mixed in a ratio of 8:1:1 and ball-milled for 5 hours to obtain a uniform slurry. The slurry is then coated onto a current collector and dried in a vacuum oven for 10 hours before being pressed into a sheet to obtain the final electrode sheet.

[0010] A third aspect of the present invention provides a battery including the electrode plates of the second aspect described above, while other components, including the separator and electrolyte, are not particularly limited.

[0011] Furthermore, the application of the flexible conductive aqueous binder allows the battery to be assembled in the following manner: in a glove box filled with argon (water value <0.1 ppm), the positive electrode shell, positive electrode plate, separator, negative electrode plate, and negative electrode shell are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. Electrolyte is then injected and the battery is sealed to obtain a coin cell.

[0012] Compared with the prior art, the beneficial effects of the present invention include at least the following: (1) The aqueous conductive emulsion binder of the present invention has a core-shell structure, with the core being a flexible copolymer component and the shell being a conductive polymer component, which can simultaneously achieve high toughness and high conductivity of the binder. High toughness endows it with the ability to adapt to volume deformation during the charging and discharging process of sulfur cathode; high conductivity is beneficial to the charge transport of active materials. Therefore, it is beneficial to improve the cycle stability and rate performance of the battery.

[0013] (2) The water-based conductive emulsion binder of the present invention deposits thiophene conductive polymers in situ on the surface of macromolecular doped emulsion particles by means of oxidative polymerization, and applies a “forced mutual solubility” effect through macromolecular acid doping, thereby increasing the compatibility between components, forming a perfect conductive network, improving the transport path of charge carriers, and significantly improving the rate performance of the battery.

[0014] (3) The aqueous conductive emulsion binder of the present invention contains abundant polar functional groups (ester group, cyano group, sulfonic acid group, etc.), which have a strong adsorption capacity for lithium polysulfides when used in sulfur cathodes, and can significantly suppress the shuttle effect. Therefore, it significantly improves the cycle performance of the battery.

[0015] (4) When preparing electrode sheets using the water-based conductive emulsion binder of the present invention, the emulsion particles deform during the rolling process, and the polymer interface molecular chains diffuse, penetrate and entangle with each other to form a fibrous network structure, which tightly binds the conductive carbon and active substances, thus achieving a low amount of binder. Attached Figure Description

[0016] Figure 1 This is a transmission electron microscope image of the aqueous conductive emulsion binder of Example 1.

[0017] Figure 2The images are scanning electron microscope (SEM) images of the positive electrode prepared in Example 1 before (a) cycling and after (b) 200 cycles.

[0018] Figure 3 Scanning electron microscope (SEM) images of the positive electrode prepared in Comparative Example 1 before (a) cycling and after (b) 200 cycles.

[0019] Figure 4 The cycle performance of the lithium-sulfur battery assembled in Example 1 is shown. Implementation

[0020] To make the inventive objectives, technical solutions, and beneficial technical effects of this application clearer, the following detailed description is provided in conjunction with embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0021] Unless otherwise specified, all reagents, materials and instruments used in the following examples and comparative examples are commercially available.

[0022] Test methods: Elongation at break test: universal testing machine; tensile test.

[0023] Test procedure: Dry the adhesive at 60℃ to prepare a 130 μm thick film. Cut the film into dumbbell-shaped strips with a length of 15 mm and a width of 3 mm. Fix the sample along its length between the upper and lower clamps of the universal testing machine. The initial distance between the upper and lower clamps is L0. The lower clamp remains stationary, and the upper clamp stretches the sample at a constant rate of 50 mm / min until the sample breaks. At this point, the distance between the upper and lower clamps is L1. The elongation at break is (L1-L0) / L0×100%.

[0024] Electronic conductivity testing: Four-probe tester.

[0025] Test procedure: Use a four-probe tester to measure the resistivity of the adhesive in Ω, using the formula: The electronic conductivity is obtained, where σ is the electronic conductivity, G is the correction factor for the sample film thickness, and D is the correction factor for the film shape and position.

[0026] 180° peel test: Universal testing machine: tensile mode test.

[0027] Test Procedure: Dry the electrode sheet in a 60℃ oven for 10 hours, cut it into strips of 2.5×5 cm, and perform a 180° peel test. Use double-sided tape to attach the cut positive electrode sheet to a 3 cm×6 cm steel plate, roll it 7 to 8 times with a small roller, and then perform a peel test using a tensile testing machine. Fix the steel plate in the lower clamp of the tensile testing machine, bend the electrode sheet 180°, clamp the positive electrode sheet with the upper clamp, and peel 50 mm at a constant rate of 25 mm / min in a direction parallel to the electrode sheet. Obtain the stress and displacement data. The adhesion force between the active material layer and the positive current collector = stress / displacement.

[0028] Rate performance testing: Xinwei Battery Testing System.

[0029] Test procedure: The test temperature is 25℃. The battery is charged to 2.8V at a constant current of 0.1C, left to stand for 30 seconds, discharged to 1.7V at 0.1C, left to stand for another 30 seconds, and then charged to 2.8V at 0.1C. The rate performance test is performed by constant current charge and discharge tests at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C for ten times each, to obtain the battery specific capacity at different rates.

[0030] Cyclic performance testing: Xinwei Battery Testing System.

[0031] Test procedure: The test temperature is 25℃. Charge at a constant current of 0.2 C to 2.8 V, let stand for 30 seconds, then discharge at 0.2 C to 1.7 V, let stand for another 30 seconds, and then charge at 0.2 C to 2.8 V. The capacity obtained by this process is the initial capacity. The cycle count is 200. Capacity retention rate = Capacity of the last cycle / Initial capacity.

[0032] Example 1.

[0033] In this embodiment, a first aspect provides a flexible conductive water-based adhesive, which is prepared by the following steps: (1) Under nitrogen or an inert atmosphere, 0.2 g sodium dodecyl sulfonate, 0.06 g sodium bisulfite, 0.1 g 1,4-butanediol diacrylate, 2 g sodium p-styrene sulfonate, 5 g butyl acrylate, 3 g p-styrene and deionized water are uniformly mixed and emulsified. After heating to the reaction temperature, 0.12 g ammonium persulfate is added. After reacting for 5 hours, 0.08 g ammonium persulfate and 0.04 g sodium bisulfite are added. After reacting for another 10 hours, a macromolecular doped emulsion with a solid content of 30 wt% is obtained. The reaction temperature is 50 °C. (2) Under nitrogen or inert atmosphere, 0.5 g of 2-vinylthiophene was doped into 15 g of macromolecular doped emulsion, and 1 g of ferric nitrate was added to continue the reaction. After 24 hours of reaction, a conductive polymer emulsion with a solid content of 25 wt% was obtained. The reaction temperature was 5 °C. Impurities were removed by adsorption with chelating resin and dialysis. The above conductive polymer emulsion was then doped again with 5% dimethyl sulfoxide and mixed with deionized water at room temperature to prepare a 5 wt% flexible conductive water-based binder.

[0034] In this embodiment, the second aspect provides a positive electrode sheet, including a current collector and a positive electrode film, wherein the positive electrode sheet is prepared by the following steps: Take active material sulfur carbon, conductive agent conductive carbon black, and the above-mentioned flexible conductive water-based binder, mix them in a ratio of 8:1:1, ball mill for 5 h to obtain a uniform slurry, then coat it on the current collector and dry it in a vacuum oven for 10 h before pressing it into a sheet to obtain the final electrode sheet product.

[0035] In this embodiment, a third aspect provides a battery, including the positive electrode sheet described in the second aspect above, wherein the battery is assembled through the following steps: In an argon-filled glove box (water content <0.1 ppm), the positive electrode shell, the aforementioned positive electrode sheet, the separator, the lithium negative electrode, and the negative electrode shell are stacked in sequence. A polypropylene film is used as the separator, which is positioned between the positive and negative electrodes to provide isolation. A mixed solution of 1 mol / L lithium bis(trifluoromethanesulfonyl)imide in ethylene glycol dimethyl ether and 1,3-dioxolane (volume ratio of the two solvents is 1:1) is injected, and 1% lithium nitrate is used as an additive as the electrolyte. The mixture is then encapsulated to obtain a coin-type lithium-sulfur battery.

[0036] The applicant further conducted cycle performance tests on the lithium-sulfur battery and obtained the following results: Figure 1 The SEM images of the positive electrode of the lithium-sulfur battery before and after 200 cycles are shown. Figure 3 The cycling curve of the lithium-sulfur battery is shown. Among them, Figure 1 (a) is a SEM image of the positive electrode of the lithium-sulfur battery before cycling, and (b) is a SEM image of the positive electrode of the lithium-sulfur battery after 200 cycles. Figure 1 As shown, the lithium-sulfur battery cathode prepared using the flexible conductive aqueous binder described in Example 1 can maintain electrode integrity even after long-term cycling, thanks to its good mechanical properties and high adhesion.

[0037] Example 2

[0038] In this embodiment, a first aspect provides a flexible conductive water-based adhesive, which is prepared by the following steps: (1) Under nitrogen or inert atmosphere, 0.2 g of octylphenol polyoxyethylene ether-10, 1 g of hydrogen peroxide, 0.1 g of divinylbenzene, 1.5 g of sodium vinyl sulfonate, 6 g of isooctyl acrylate, 2.5 g of butadiene and deionized water are uniformly mixed and emulsified. After heating to the reaction temperature, 3 g of ferrous sulfate is added. After reacting for 8 hours, 3 g of ferrous sulfate and 1 g of hydrogen peroxide are added. After reacting for another 12 hours, a macromolecular doped emulsion with a solid content of 25 wt% is obtained. The reaction temperature is 35 °C. (2) Under nitrogen or inert atmosphere, 0.3 g of 3,4-vinyldioxythiophene was doped into 17 g of macromolecular doped emulsion, and 0.75 g of ferric sulfate was added to continue the reaction. After 15 hours of reaction, a conductive polymer emulsion with a solid content of 20 wt% was obtained, and the reaction temperature was 5 °C. The above conductive polymer emulsion was then doped with 5% dimethyl sulfoxide and deionized water was added to prepare a 5 wt% flexible conductive water-based binder at room temperature.

[0039] In this embodiment, the second aspect provides a positive electrode sheet, including a current collector, the binder described in the first aspect, and a positive electrode film, wherein the preparation steps of the positive electrode sheet are the same as in Embodiment 1.

[0040] In this embodiment, a third aspect provides a battery, including the positive electrode sheet of the second aspect described above, and the battery assembly steps are the same as in Embodiment 1.

[0041] Example 3

[0042] In this embodiment, a first aspect provides a flexible conductive water-based adhesive, which is prepared by the following steps: (1) Under nitrogen or inert atmosphere, 0.2 g of nonylphenol polyoxyethylene ether ammonium sulfate, 0.08 g of sodium bisulfite, 0.1 g of divinylbenzene, 1.8 g of sodium allyl sulfonate, 5.7 g of butyl acrylate, 2.5 g of acrylonitrile and deionized water are uniformly mixed and emulsified. After heating to the reaction temperature, 0.16 g of potassium persulfate is added. After reacting for 6 hours, 0.08 g of potassium persulfate and 0.04 g of sodium bisulfite are added. After reacting for another 10 hours, a macromolecular doped emulsion with a solid content of 28 wt% is obtained. The reaction temperature is 45 °C. (2) Under nitrogen or inert atmosphere, 0.4 g of 2-vinylthiophene was doped into 16 g of macromolecular doped emulsion, and 0.6 g of ferric nitrate was added to continue the reaction. After 48 hours of reaction, a conductive polymer emulsion with a solid content of 23 wt% was obtained, and the reaction temperature was 5 °C. The above conductive polymer emulsion was then doped with 5% dimethyl sulfoxide and deionized water was added to prepare a 5 wt% flexible conductive water-based binder at room temperature.

[0043] In this embodiment, the second aspect provides a positive electrode sheet, including a current collector, the binder described in the first aspect, and a positive electrode film, wherein the preparation steps of the positive electrode sheet are the same as in Embodiment 1.

[0044] In this embodiment, a third aspect provides a battery, including the positive electrode sheet of the second aspect described above, and the battery assembly steps are the same as in Embodiment 1.

[0045] Example 4

[0046] In this embodiment, a first aspect provides a flexible conductive water-based adhesive, which is prepared by the following steps: (1) Under nitrogen or inert atmosphere, 0.2 g nonylphenol polyoxyethylene ether ammonium sulfate, 0.05 g sodium bisulfite, 0.1 g N,N'-methylenebisacrylamide, 2 g sodium p-styrene sulfonate, 5 g butyl acrylate, 3 g p-styrene and deionized water are uniformly mixed and emulsified. After heating to the reaction temperature, 0.1 g ammonium persulfate is added. After reacting for 4 hours, 0.1 g ammonium persulfate and 0.05 g sodium bisulfite are added. After reacting for another 8 hours, a macromolecular doped emulsion with a solid content of 32 wt% is obtained. The reaction temperature is 40 °C. (2) Under nitrogen or inert atmosphere, 0.4 g of 3-hexylthiophene was doped into 14.5 g of macromolecular doped emulsion, and 1.6 g of ferric nitrate was added to continue the reaction. After 10 hours of reaction, a conductive polymer emulsion with a solid content of 28 wt% was obtained, and the reaction temperature was 8 °C. The above conductive polymer emulsion was then doped with 5% dimethyl sulfoxide and deionized water was added to prepare a 5 wt% flexible conductive water-based binder at room temperature.

[0047] In this embodiment, the second aspect provides a positive electrode sheet, including a current collector, the binder described in the first aspect, and a positive electrode film, wherein the preparation steps of the positive electrode sheet are the same as in Embodiment 1.

[0048] In this embodiment, a third aspect provides a battery, including the positive electrode sheet of the second aspect described above, and the battery assembly steps are the same as in Embodiment 1.

[0049] Example 5

[0050] In this embodiment, a first aspect provides a flexible conductive water-based adhesive, which is prepared by the following steps: (1) Under nitrogen or an inert atmosphere, 0.2 g sodium dodecyl sulfonate, 0.07 g sodium bisulfite, 0.1 g N,N'-methylenebisacrylamide, 1.8 g sodium allyl sulfonate, 5.2 g ethyl acrylate, 3 g p-styrene and deionized water were uniformly mixed and emulsified. After heating to the reaction temperature, 0.14 g ammonium persulfate was added. After reacting for 5 hours, 0.08 g ammonium persulfate and 0.04 g sodium bisulfite were added. After reacting for another 12 hours, a macromolecular doped emulsion with a solid content of 30 wt% was obtained. The reaction temperature was 50 °C. (2) Under nitrogen or inert atmosphere, 0.4 g of 3-hexylthiophene was doped into 15 g of macromolecular doped emulsion, and 0.8 g of ferric chloride was added to continue the reaction. After 24 hours of reaction, a conductive polymer emulsion with a solid content of 25 wt% was obtained, and the reaction temperature was 10 °C. The above conductive polymer emulsion was then doped with 5% dimethyl sulfoxide and deionized water was added to prepare a 5 wt% flexible conductive water-based binder at room temperature.

[0051] In this embodiment, the second aspect provides a positive electrode sheet, including a current collector, the binder described in the first aspect, and a positive electrode film, wherein the preparation steps of the positive electrode sheet are the same as in Embodiment 1.

[0052] In this embodiment, the third aspect provides a battery, including the positive electrode sheet of the second aspect described above, and the battery pack conversion steps are the same as in Embodiment 1.

[0053] Comparative Example 1

[0054] In this Comparative Example 1, a lithium-sulfur battery cathode and a battery were prepared, which included the macromolecular doped emulsion binder from Example 1.

[0055] The method for preparing the positive electrode of the lithium-sulfur battery is as follows: The sulfur-carbon tube composite material, conductive carbon black, and macromolecular doped emulsion were dispersed in a dispersant water at a mass ratio of 8:1:1. The mixture was ball-milled for 5 hours to obtain a uniform slurry, which was then coated onto a current collector and dried in a vacuum oven for 10 hours before being pressed into a sheet to obtain the final electrode sheet.

[0056] The assembly method of the lithium-sulfur battery is as follows: In an argon-filled glove box (water content <0.1 ppm), the positive electrode shell, the aforementioned positive electrode sheet, the separator, the lithium negative electrode, and the negative electrode shell are stacked in sequence. A polypropylene film is used as the separator, which is positioned between the positive and negative electrodes to provide isolation. A mixed solution of 1 mol / L lithium bis(trifluoromethanesulfonyl)imide in ethylene glycol dimethyl ether and 1,3-dioxolane (volume ratio of the two solvents is 1:1) is injected, and 1% lithium nitrate is used as an additive as the electrolyte. The mixture is then encapsulated to obtain a coin-type lithium-sulfur battery.

[0057] The applicant further conducted cycle performance tests on the lithium-sulfur battery and obtained the following results: Figure 2 The image shows SEM images of the positive electrode of the lithium-sulfur battery before and after 200 cycles. Figure 2 (a) is a SEM image of the positive electrode of the lithium-sulfur battery before cycling, and (b) is a SEM image of the positive electrode of the lithium-sulfur battery after 200 cycles. Figure 2 As shown, the lithium-sulfur battery cathode assembled using the macromolecular doped emulsion binder of Comparative Example 1 exhibited significant agglomeration after long-term cycling, which would make it difficult to achieve the full performance of the battery.

[0058] Verification of Examples

[0059] In this embodiment, the flexible conductive water-based adhesives described in Examples 1 to 5 and the adhesive macromolecule-doped emulsion adhesive used in Comparative Example 1 were first tested for elongation at break, 180° peel test, and electronic conductivity, and the test results are shown in Table 1.

[0060] Table 1 Physical properties of water-based adhesives sample Elongation at break (%) <![CDATA[Peel strength (N mm -1 )]]> <![CDATA[electronic conductivity (S cm -1 )]]> Example 1 83 0.35 1.17 Example 2 125 0.46 0.81 Example 3 105 0.40 0.95 Example 4 89 0.33 1.05 Example 5 101 0.39 0.97 Comparative Example 1 176 0.50 <0.01 As shown in Table 1, the flexible conductive water-based binders of Examples 1-5 exhibited an elongation at break exceeding 80%, demonstrating good toughness, while the binder in Comparative Example 1 showed even superior toughness. However, the macromolecular doped emulsion of the binder in Comparative Example 1 was non-conductive, while the electronic conductivity of the water-based binders for lithium-sulfur batteries of Examples 1-5 was around 1 S / cm. Furthermore, the peel strength of the flexible conductive water-based binders of Examples 1-5 was slightly lower than that of Comparative Example 1, but the difference was not significant.

[0061] Furthermore, the applicant conducted rate performance tests and cycle performance tests on the lithium-sulfur batteries assembled in Examples 1-5 and Comparative Example 1, and obtained the test results shown in Table 2.

[0062] Table 2 Electrochemical performance of lithium-sulfur batteries assembled with different aqueous binders sample <![CDATA[Discharge specific capacity at 0.1C (mAh g -1 )]]> <![CDATA[Discharge specific capacity at 2C (mAh g -1 )]]> Volume retention rate after 200 laps (%) Example 1 1257 849 79.8 Example 2 1201 769 80.9 Example 3 1228 819 83.0 Example 4 1248 836 81.7 Example 5 1239 828 82.6 Comparative Example 1 1106 606 52.6 As can be seen from the data in Table 2, the coin cells assembled with the flexible conductive aqueous binders of Examples 1-5 exhibit significantly higher rate performance than Comparative Example 1. Furthermore, the initial discharge capacity of the coin lithium-sulfur batteries assembled with the flexible conductive aqueous binders of Examples 1-5 is higher than that of Comparative Example 1; and the capacity retention rate of the coin lithium-sulfur batteries assembled with the flexible conductive aqueous binders of Examples 1-5 after 200 cycles at 0.2 C is also much higher than that of Comparative Example 1.

[0063] The present invention has been described by the above-described embodiments; however, these embodiments are merely examples for implementing the present invention. It must be noted that the disclosed embodiments do not limit the scope of the present invention. Conversely, modifications and equivalents contained within the spirit and scope of the claims are included within the scope of the present invention.

Claims

1. A flexible conductive water-based adhesive, characterized in that, The aqueous emulsion with a core-shell structure is prepared by emulsion polymerization and electrostatic doping. The core is formed by emulsion polymerization of unsaturated sulfonate monomers, acrylate monomers, and unsaturated monomers with excellent resistance to organic electrolytes into a macromolecular doped aqueous emulsion. The shell is a conductive polymer formed by oxidative polymerization of thiophene monomers. The unsaturated monomers with excellent resistance to organic electrolytes are styrene or acrylonitrile. The mass ratio of macromolecular doped aqueous emulsion to thiophene monomer is 50:1~3. The flexible conductive water-based adhesive is prepared by the following method, including the following steps: (1) Under an inert atmosphere, 0.1-0.3 parts by weight of emulsifier, 0.1-0.2 parts by weight of reducing component of redox initiator, 0.1-0.5 parts by weight of crosslinking agent, 15-30 parts by weight of unsaturated sulfonate monomer, 30-60 parts by weight of acrylate monomer, 25-40 parts by weight of unsaturated monomer with excellent resistance to organic electrolyte and deionized water are uniformly mixed and emulsified. After heating to 30-70°C, 0.2-0.4 parts by weight of oxidizing component of redox initiator is added. After reacting for 4-8 hours, 0.2-0.4 parts by weight of oxidizing component of redox initiator and 0.1-0.2 parts by weight of reducing component of redox initiator are added, and the reaction is continued for 6-12 hours to obtain a macromolecular doped emulsion with a solid content of 25 wt%-40 wt%. (2) Under an inert atmosphere, 2-6 parts of thiophene monomer are doped into 94-98 parts of macromolecular doped emulsion, and 2-5 parts of oxidant are added. The mixture is stirred and reacted at 0-20°C for 24-72 hours to obtain a conductive polymer emulsion with a solid content of 15 wt%-30 wt%. The emulsion is then purified by adsorption with chelating resin and dialysis. The conductive polymer emulsion is then subjected to secondary doping with 5% dimethyl sulfoxide and mixed with deionized water at room temperature to prepare a 5 wt% flexible conductive waterborne binder.

2. The flexible conductive water-based adhesive according to claim 1, characterized in that, The unsaturated sulfonate monomer is one or more of sodium p-styrene sulfonate, sodium vinyl sulfonate, and sodium allyl sulfonate; the acrylate monomer is one of butyl acrylate, ethyl acrylate, and isooctyl acrylate.

3. The flexible conductive water-based adhesive according to claim 1, characterized in that, The thiophene monomer is one of 3,4-ethylenedioxythiophene, 2-vinylthiophene, and 3-hexylthiophene.

4. The flexible conductive water-based adhesive according to claim 1, characterized in that, The oxidizing component of the redox initiator is one of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the reducing component of the redox initiator is one of sodium thiosulfate, sodium bisulfite, and ferrous sulfate; and the molar ratio of the oxidizing component to the reducing component of the initiator is 1~3:

1.

5. The flexible conductive water-based adhesive according to claim 1, characterized in that, The emulsifier is one or more of sodium dodecyl sulfate, nonylphenol polyoxyethylene ether ammonium sulfate, and octylphenol polyoxyethylene ether.

6. The flexible conductive water-based adhesive according to claim 1, characterized in that, The crosslinking agent is one or more of divinylbenzene, 1,4-butanediol diacrylate, and N,N'-methylenebisacrylamide.

7. The flexible conductive water-based adhesive according to claim 1, characterized in that, The oxidant is one of ferric sulfate, ferric chloride, and ferric nitrate.

8. An electrode sheet, said electrode sheet comprising an active material, a binder, and a conductive agent, characterized in that, The adhesive is the adhesive according to any one of claims 1-7.

9. A battery, said battery comprising a positive electrode, a separator, an electrolyte, and a negative electrode, characterized in that, The positive electrode is the electrode as described in claim 8.

Citation Information

Patent Citations

  • Lithium-sulfur battery binder and preparation method and application thereof

    CN111092226A

  • Preparation method of conductive binder, battery pole piece and battery

    CN115995557A